Effects of constraint between filaments on the radial compression properties of poly (l-lactic acid) self-expandable braided stents. (January 2021) - Zhao, Gutian; Liu, Muqing; Deng, Dongwen; Tian, Yuan; Cheng, Jie; Wu, Gensheng; Zhang, Yi; Ni, Zhonghua
Abstract: With the application of bioresorbable materials in self-expandable braided stent, current analytical model for radial compression property of the stent is not applicative if considering the constraint between the polymeric filaments. Poly (l -lactic acid) (PLLA) is one of the broadly used bioresorbable materials in stents due to its superior biocompatibility and mechanical properties. The radial compression properties of PLLA braided stents were investigated by considering two types of constraints between filaments in this work. Weak constraint indicates the friction between filaments of PLLA stents and strong constraint indicates the close looped end (extremity configuration) of PLLA stents. It is found that the radial stiffness can be enhanced by two types of constraints, and strong constraint improves the peak compression force slightly in the radial compression behavior of PLLA braided stents. This work provides suggestions for the study of PLLA braided stents theoretical development. Highlights: The constraint between PLLA filaments needing to be considered in theoretical model. The friction between filaments can enhance the radial stiffness of PLLA braided stent. The close looped end of stent can enhance the radial stiffness and improve the peak compression force.